Logistics support of the domestic market of oil crop and oil - Strashynska, Larysa (My University, 2022)
The article examines the main results of logistical support of the domestic market of oilseeds and oil. The dynamics of shipments of oil crops and their processing products through the ports of Ukraine during the 2020/21 marketing year (MY) were analyzed. It was determined that the share of sunflower oil in the structure of the shipment occupies a significant specific weight, in contrast to rapeseed and soybean oil, where the main product of the shipment was rapeseed and soybean. The indicators of transshipment of vegetable oil during 2019–2021 were studied (with a cumulative total by month), which indicate that although the situation improved in 2020 compared to 2019, but in 2021 compared to 2020, transshipment volumes significantly decreased. The indicators of transshipment of vegetable oil by types of stevedoring companies of all forms of ownership were analyzed in terms of shipping directions in 2021 compared to 2020. The most powerful ports of Ukraine were determined based on transshipment results and their specific weight, as well as key shipping directions. The dynamics of transportation of oil-fat complex cargoes by railway transport was analyzed. It was revealed that in the structure of railway transportation of sunflower seeds for the period 2018–2021, priority was given to internal communication, and in the structure of transportation of vegetable oil, the export route traditionally prevailed. The main problems related to the implementation of railway transportation, including those related to the activities of JSC "Ukrzaliznytsia", are highlighted. The measures, the practical implementation of which will allow for an increase in the volume of cargoes transportation of oil and fat industry and processing products, are justified, and will also contribute to the improvement of logistics support in the market of oilseeds and oil in general. У статті розглянуто основні результати логістичного забезпечення вітчизняного ринку олійних культур та олії. Проаналізовано динаміку відвантажень олійних культур та продуктів їх переробки через порти України протягом 2020/21 маркетингового року (МР). Визначено, що частка соняшникової олії в структурі відвантаження займає значну питому вагу на відміну від ріпакової та соєвої олії, де основним продуктом відвантаження були ріпак та соя. Досліджено показники перевалки рослинної олії протягом 2019–2021 рр. (з наростаючим підсумком по місяцях), які свідчать про те, що хоча у 2020 р. порівняно з 2019 р. ситуація покращилася, але у 2021 р. порівняно з 2020 р. обсяги перевалки суттєво знизились. Проаналізовано показники перевалки рослинної олії за видами стивідорних компаній всіх форм власності в розрізі напрямків відвантаження у 2021 р. порівняно з 2020 р. Визначено найпотужніші порти України за підсумками перевалки та їх питому вагу, а також ключові напрями відвантажень. Проаналізовано динаміку перевезень вантажів олійно-жирового комплексу залізничним транспортом. Виявлено, що в структурі залізничних перевезень насіння соняшника за період 2018–2021 рр. пріоритетним було внутрішнє сполучення, а в структурі перевезень рослинної олії традиційно переважало експортне спрямування. Виокремлено основні проблеми щодо здійснення залізничних перевезень, в тому числі, пов’язані з діяльністю АТ «Укрзалізниця». Обґрунтовано заходи, практична реалізація яких дозволить забезпечити збільшення обсягів перевезень вантажів олійно-жирової промисловості та продуктів переробки, а також сприятиме покращенню логістичного забезпечення на ринку олійних культур та олії в цілому.
Keywords: кафедра маркетингу; market of oil crops and oil; cargo transportation; cargo handling volumes; sea ports; transportation of products; railway transport; indicators of oil transshipment; state stevedoring companies; ринок олійних культур та олії; перевезення вантажів; обсяги вантажообробки; морські порти; транспортування продукції; залізничний транспорт; показники перевалки олії; державні стивідорні компанії